A model for estimating recovery rates and collateral haircuts for bank loans - Esa Jokivuolle; Samu Peura (Bank of Finland, 2000)
We present a model of risky debt in which collateral value is correlated with the possibility of default.The model is then used to study: 1) the expected amount of debt recovered in the event of default as a function of collateral; and 2) the amount of collateral needed to mitigate the riskiness of a loan to a desired degree.The results obtained could prove useful for estimating recovery rates required by many popular models of credit risk and for determining collateral haircuts in debt transactions.The analysis also generates testable predictions of the behaviour of historical recovery rates of risky debt when collateral is involved.Regulators might benefit from the analysis in developing capital adequacy requirements and reviewing banks' lending standards relative to current collateral values.
URN:NBN:fi:bof-20140807462
Keywords: 330